Pengaruh Budaya Organisasi, Kepemimpinan dan Kompensasi terhadap Kinerja Karyawan di Forever Hope Digital Printing Surabaya dengan Kepuasan Kerja sebagai Variabel Intervening - Matheous Tamonsang; Shafa Salsabilla Windarto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study is to determine how organizational culture, leadership, and compensation impact employee performance at Forever Hope Digital Printing Surabaya, with job satisfaction as an intermediary. This research was conducted quantitatively with a simple random sampling method, and questionnaires were distributed to 64 respondents. Data analysis was conducted using descriptive analysis and path analysis techniques, which were processed using IBM SPSS Version 20. The results showed that organizational culture, leadership, and individual compensation had a positive impact on employee performance at Forever Hope Digital Printing Surabaya, although not significantly. However, leadership and compensation have a positive and significant impact on employee job satisfaction in the company. In addition, job satisfaction has a positive and significant impact on employee performance. Thus, job satisfaction serves as a mediator that explains the relationship between organizational culture, leadership, and compensation with employee performance at Forever Hope Digital Printing Surabaya.